2012
DOI: 10.2459/jcm.0b013e32835794c1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation services in Ontario

Abstract: Most cardiac rehabilitation programs offered alternative models of care, such as home-based rehabilitation. Cardiac rehabilitation sites are well integrated within their community, enabling smooth postcardiac rehabilitation transitions for patients. Cardiac rehabilitation programs continue to offer proven comprehensive components, while simultaneously attempting to adapt to meet the needs of patients with other chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Major barriers (again reported on the same 5-point scale as per above) also included patient referral (3.2), and lack of equipment (2.7). In the provincial survey 76 , results showed that in addition to those shown in Table 1, 68% of programs also offered psychosocial services. There were also 2 narrative reviews published describing CR status in Canada 42,77 .…”
Section: Cr Delivery In North Americamentioning
confidence: 90%
“…Major barriers (again reported on the same 5-point scale as per above) also included patient referral (3.2), and lack of equipment (2.7). In the provincial survey 76 , results showed that in addition to those shown in Table 1, 68% of programs also offered psychosocial services. There were also 2 narrative reviews published describing CR status in Canada 42,77 .…”
Section: Cr Delivery In North Americamentioning
confidence: 90%
“…In general, patients attend CR twice per week for over 4–6 months,8 during which time they receive the well-established core components of the model, namely risk factor assessment, structured exercise training, patient education, as well as dietary and psychosocial counseling 9. CR participation is associated with 20% lower cardiovascular mortality,10 with greater participation associated with greater benefits 11.…”
Section: Introductionmentioning
confidence: 99%
“…CR services are covered through provincial health insurance in these jurisdictions. CR programming is guided by the Canadian Association of Cardiac Rehabilitation guidelines [20], averaging five months in duration, with a median of two supervised sessions per week [21]. Overall there were 17 cardiac wards at these hospitals, as one hospital had three cardiac wards, and four hospitals had two cardiac wards each ( i.e.…”
Section: Methodsmentioning
confidence: 99%